Archean and Paleoproterozoic zircons in Paleozoic sandstones in southern New Zealand: evidence for remnant Nuna supercontinent and Ur continent rocks within Zealandia. Issue 8 (17th November 2022) - Adams, C. J.; Ramsay, W. R. H.
Abstract: Detrital zircon age patterns are reported from quartz sandstones and metaquartzites in the Russet and Wangapeka formations (Western Province, Takaka Terrane) in Fiordland and northwest Nelson, and the Pegasus Group on Stewart Island. The latter indicate a possible maximum early Carboniferous depositional age with a significant Lower Devonian zircon component that suggests a source on the Campbell Plateau or Marie Byrd Land, West Antarctica. In contrast, Russet Formation ages indicate a correlation with Upper Ordovician, Wangapeka Formation quartz sandstones in northwest Nelson. These zircon age patterns have two major groups: late Mesoproterozoic (1200–1000 Ma) of Rodinia origin and Cambrian–late Neoproterozoic (700–500 Ma) of early Gondwana derivation. Both groups have local Zealandia provenances. In addition, there are unusually high proportions (to 20%) of early Paleoproterozoic and Archean zircons, 3500–2000 Ma, with significant age components, 2550–2450 Ma and ca 2800 and 2650 Ma, which are characteristic of an Expanded-Ur continent. Their high proportions of euhedral grains indicate a local source within a postulated Archean basement block at or near the eastern margin of the Takaka Terrane. A proposed Rodinia supercontinent reconstruction locates this Precambrian basement as a Zealandia component placed between Gawler and North Australia cratons of Australia and Yangtze Block of the South China Craton. KEY POINTS: Pegasus Group, metaquartzites, Stewart Island are not correlated with the Russet Formation, Fiordland but are an Upper Devonian or lower Carboniferous sedimentary unit. Russet Formation high-grade metasandstones in Fiordland are correlated with the lower-grade and fossiliferous Upper Ordovician Wangapeka Formation in Nelson. Upper Ordovician sandstones in Western Province, New Zealand contain unusually high proportions of Neoarchean euhedral detrital zircons that suggest a local Zealandia source. An Archean block is proposed within the Rodinia supercontinent, between the Gawler and North Australia cratons of Australia and Yangtze Block of the South China Craton.